Analysis of the Main Character Costumes in ‘Enola Holmes’ Movie using CS Peirce’s Theory - Ardia Idris; Muhammad Hasbi (GLENS: Global English Insights Journal, 2024)
This study aims to analyze the costumes that the main character wears in the movie ‘Enola Holmes’ by using Charles Sanders (CS) Peirce’s theory. The data in this study was collected by watching the movies several times and taking notes on the costumes worn by Enola Holmes, the main character in this movie. The data analysis was done by identifying the signs in the costumes and interpreting their meanings based on CS Peirce’s semiotic theory, which divides signs into icons, indexes, and symbols. The result of this study shows that Enola Holmes’ costumes function as icons, indexes, and symbols. As icons, the costumes directly represent the Victorian era and Enola’s various disguises. As indexes, the costumes reflect Enola’s actions, emotions, and experiences. Furthermore, as symbols, the costumes convey meanings related to gender roles, courage, independence, and family heritage. This study helps in gaining an understanding of how film costumes can be used to communicate storylines and to develop characters.